2014
DOI: 10.1002/14651858.cd007287.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-specific active immunotherapy for ovarian cancer

Abstract: We conclude that despite promising immunological responses, no clinically effective antigen-specific active immunotherapy is yet available for ovarian cancer. Results should be interpreted cautiously as there was a significant lack of relevant information for the assessment of risk of bias in both RCTs and non-RCTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 96 publications
0
12
0
Order By: Relevance
“…In addition, immunotherapy was reported to effectively improve patients' autonomic anticancer immunity, strengthen their physique, reduce chemotherapy resistance, enhance the effect of chemotherapy on ovarian cancer and extend the valid period of survival (10). Antigen-specific active immunotherapy aims to induce tumor-antigen-specific antitumor immune responses, and has emerged as an alternative treatment for ovarian cancer (36). In the process of an immune response, tumor antigens are processed by APCs and presented to CTLs (14).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, immunotherapy was reported to effectively improve patients' autonomic anticancer immunity, strengthen their physique, reduce chemotherapy resistance, enhance the effect of chemotherapy on ovarian cancer and extend the valid period of survival (10). Antigen-specific active immunotherapy aims to induce tumor-antigen-specific antitumor immune responses, and has emerged as an alternative treatment for ovarian cancer (36). In the process of an immune response, tumor antigens are processed by APCs and presented to CTLs (14).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated immune response but clinical benefit rate was minimal in all of these studies. The vaccination approach is not used in clinical practice nowadays [11].…”
Section: (3) Targeting the Tumor Environment (Immune Inhibitory Mechamentioning
confidence: 99%
“…To date, we have an efficacious vaccination available against the nine most important HPV types (HPV 6,11,16,18,31,33,45,52,and 58) [27]; however, despite better prevention strategies, cervical cancer is still not sufficiently manageable worldwide with a stagnating mortality rate. Most cancers in the developed world present in early FIGO stage IA1-IIA, while primary metastatic disease is uncommon.…”
Section: Cervical Cancermentioning
confidence: 99%
“…This approach can be efficiently employed for the eradication of residual cancer cells and prevention or delay of tumor relapse (9). An example is the case of solid tumors, where antigen-specific immunotherapy has emerged as a promising approach (10)(11)(12). One of the key players in mediating immune response are the dendritic cells (DCs) as they are specialized in priming naive helper and cytotoxic T-lymphocytes and directly trigger natural killer (NK) cell function (13).…”
Section: Introductionmentioning
confidence: 99%